1986
DOI: 10.1508/cytologia.51.171
|View full text |Cite
|
Sign up to set email alerts
|

Cytological effects of pesticides. XVI Effect of the insecticide rotenone on root-mitosis of Vicia faba.

Abstract: Rotenone (1) is a component of the roots of several plant species: Derris ellip tica, Lonchocarpus utilis, L. urucu (Haley 1978) and Millettia pachycarpa (Singhal et al. 1982). Derris and cube resins have been approved for use as insecticides on fruits, vegetables, and forage crops and for indoor and outdoor use to control various pests, including mosquitos and their larvae (EPA 1972). Derris roots have been used for clearing ponds of fish (Chowdhury et al. 1981). Rotenone has also an antifeedant effect to sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In the present study, only the highest concentration of NP was toxic. Dichlorvos, the active ingredient in NP was shown to decrease the mitotic index of Vicia faba root tip meristem cells treated with it (Amer & Ali, 1986;Kontek et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the present study, only the highest concentration of NP was toxic. Dichlorvos, the active ingredient in NP was shown to decrease the mitotic index of Vicia faba root tip meristem cells treated with it (Amer & Ali, 1986;Kontek et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…32-250 µg ml -1 ) was shown to decrease the MI and to increase chromosomal aberrations in Vicia faba meristem cells (Amer & Ali, 1986). Dichlorvos was mutagenic in the Ames salmonella mutagenicity assay and other tests using bacteria or animal www.ccsenet.org/enrr Environment and Natural Resources Research Vol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denmart also induced chromosome lagging, multinucleates and micronucleates. The insecticide rotenone induced disturbed meta-and anaphases in a high percentage, as well as chromosome stickiness, lagging chromosomes and ana-telophase bridges (Amer and Mikhael 1986). C-mitosis indicated that the chemical caused inhibition of spindle formation similar to the effect of colchicine (Badr 1988).…”
Section: Discussionmentioning
confidence: 97%
“…However, 100 mg/l concentration was toxic and only 25 and 50 mg/l at 48 h duration reduced the percentage of prophase and, 50 mg/l at the same duration increased anaphase cells significantly. While tridemorph (Cortes et al 1982) and thiram (Vera Lopez et al 1990) fungicides effected the percentage of the mitotic stages, rotenone (Amer and Mikhael 1986) and racer (Yüzbaşıoglu et al 2003) did not effected. Badr (1988) showed that dithane fungicide induced low frequencies of prophase in Allium cepa root tips.…”
Section: Discussionmentioning
confidence: 98%